The Resonance 107.3 FM radio art collection: Towards an archive methodology of radio as resonance. (1st October 2016) - Nielsen, Katrine Pram; Kreutzfeldt, Jacob
This article investigates the collection of Resonance 107.3 FM, which has recently become digitally accessible for research at the British Library Sound Archive. Documenting the full extent of a 28-day event by the London Musicians Collective (LMC) in 1998, the collection offers unique insight into early British community radio and practises of radio art. Based on research in the British Library Sound Archive, as well as on interviews with archivists and broadcasters, the article presents the collection and discusses its significance as an experiment in the aesthetic, social and political implications of radiophonic mediation. Building on Anna Friz's idea of radio as resonance, the study develops an approach to the archive not as a collection of programme objects but as sonic articulations of past resonant situations. This introduces a method in archival work open to the resonances of these situations found in metadata as well as in memories and texts. Applying this method of recalling, describing and reflecting to three examples of live experimentation from the Resonance 107.3 FM collection, this article illustrates that archives of minor media and practises in community and art radio are valuable resources for reimagining contemporary and future media practices.